EFEK LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP LOYALITAS GURU PADA SEKOLAH WIDYA BATAM - Lutfi Erwin Lubis; Surya Tegar Widjiantoro (LP2M-Institut Agama Islam Abdullah Said Batam, 2021)
The purpose of this study was to determine and analyze the effect of the work environment and compensation on teacher loyalty at the Widya Batam School. The research method used is a survey method with a causal technique because of the influence of several variables on teacher loyalty. The research population is teachers at the Widya Batam School of 137 teachers. The sample size taken is 102 teachers, with the sampling technique using the Slovin formula. This study uses a questionnaire instrument to measure three variables: work environment, compensation, and loyalty. These instruments were tested before being used to collect data, and the results of each instrument were valid and reliable. The data analysis technique used path analysis, which was used to test the significance of each path coefficient. The result of this study is that there is a significant direct effect between work environment on loyalty, and compensation on loyalty. Loyalty is the dependent variable. Work environment and compensation as important variables that affect loyalty, therefore it is suggested that the work environment and compensation should receive attention from the leaders at Widya School in order to increase teacher loyalty.